PHILOSOPHICAL AND PEDAGOGICAL PRECONDITIONS AND DEVELOPMENT ALGORITHM OF THE ASCENT FROM THE ABSTRACT TO THE CONCRETE IN V. V. DAVIDOV'S DIDACTICS - N. K. Chapayev (Russian State Vocational Pedagogical University, 2015)
The paper considers the problem of implementing the method of the ascent from the abstract to the concrete in education. The author emphasizes the interrelation between pedagogy and philosophy, as well as the need for their cooperation especially at the time of considerable changes in social and educational spheres.The poly-modal conceptual nature of the abstract and concrete makes it possible to attribute to them respectively the positive and negative values. By analogy with the «bad infinity», the author introduces the concepts of «bad abstract» and «abstract pedagogy» typical for the modern educational practices disregarding the specifics of the concrete areas.The historical and logical analysis of implementing the method in the Russian pedagogy demonstrates that, in spite of its fairly long development history, a systematic technological formalization can be found only in V. V. Davydov's didactics.Based on V. V. Davydov's concept of developing education, the author makes the following conclusion: as a cognitive method, the ascent from the abstract to the concrete develops theoretical thinking, in-depth understanding, personal attitude to the acquired knowledge and adequate behavior strategies. Therefore, the given method facilitates harmonious personal development.